English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Find the equation for the line that is parallel to the line with the equation y= 2/3x + 3 passing through the point (0,-1)

2006-11-08 11:30:05 · 9 answers · asked by The Ultimate Answerer 3 in Science & Mathematics Mathematics

9 answers

The slope of the line y = 2/3x + 3 is m = 2/3
The slopes of parallel lines are equal; therefore, the slope of the new line is m = 2/3
Since (0,-1) is the y-intercept that means b = -1 and you can now write the equation of the line
y = mx + b
Answer: y = 2/3x - 1

2006-11-08 11:33:40 · answer #1 · answered by MsMath 7 · 4 4

Okay, this line must have the equation y = 2/3x + A, where A is the unknown. This is because the slope 2/3 is the same if they're parallel. We know that it passes through (0, -1), so that means -1 = 2/3(0) + A . Now that we know A = -1, we have the solution y = 2/3x - 1.

2006-11-08 19:36:30 · answer #2 · answered by Scythian1950 7 · 1 1

Parallel lines have the same slope, so the equation you want starts out

y = (2/3)x + something. y = (2/3)x + b.

To find the b, plug in the point you know the line goes through:

y = (2/3)x + b
-1 = (2/3)(0) + b
-1 = b

That gives you y = (2/3)x -1.

That was the hard way. If you know that the b is the y-intercept and that (0, -1) is a point on the y-axis, then you know that b is -1 and just write the equation.

2006-11-08 19:35:57 · answer #3 · answered by Philo 7 · 2 1

y= 2/3x + 3

y=2/3x+b

-1=2/3(0)+b

-1=0+b

-1=b

y=2/3x-1

2006-11-11 03:31:12 · answer #4 · answered by Raina 2 · 0 0

This is very simple, in fact y=mx+q and q means the value at which the line crosses the y axis. And (0,-1) is on y axes so q must be -1.
in fact -1=2/3(0)-1.

2006-11-08 19:44:21 · answer #5 · answered by sparviero 6 · 0 1

m = 2/3 (slope)

since you said parallel:

y - (-1) = 2/3(x-0)
y + 1 = 2/3x
y = 2/3x - 1

2006-11-08 19:34:59 · answer #6 · answered by naglibog 2 · 2 0

' slope m = 2/3

y - (-1) = 2/3(x-0)
y + 1 = 2/3x
y = 2/3x - 1

2006-11-09 15:21:07 · answer #7 · answered by locuaz 7 · 1 1

y = 2/3x - 1

2006-11-08 19:35:09 · answer #8 · answered by Grilled cheese lover 2 · 2 0

-1=2/3*0+b
-1=b
y=2/3x-1

i think

2006-11-08 19:36:32 · answer #9 · answered by justme 6 · 1 0

fedest.com, questions and answers